Preparation of magnetic core–shell nanoflower Fe3O4@MnO2 as reusable oxidase mimetics for colorimetric detection of phenol. Issue 4 (7th January 2015) - Xiong, Yuhao; Chen, Siheng; Ye, Fanggui; Su, Linjing; Zhang, Cong; Shen, Shufen; Zhao, Shulin
Abstract : In this paper, magnetic core–shell nanoflower Fe3 O4 @MnO2 were fabricated via a solvothermal method. Abstract : In this paper, magnetic core–shell nanoflowers Fe3 O4 @MnO2 were fabricated via a solvothermal method. We demonstrated that the as-synthesized magnetic nanoflowers Fe3 O4 @MnO2 possess intrinsic oxidase-like activity in a wide pH range and can catalytically oxidize 4-aminoantipyrine (4-AAP) and phenol substrates to form pink color products without the requirement for additional oxidizing agents. On the basis of this phenomenon, a simple colorimetric method for the determination of phenol was developed. A wide linear detection range can be obtained from 1.0 μM to 120 μM ( R 2 = 0.9962) with a detection limit of 0.15 μM. And the method was applied to determine phenol in wastewater with good recoveries ranging from 96.0 to 101.5%. Furthermore, benefitting from chemical stability and easy recovery (by simple magnetic separation) of Fe3 O4 @MnO2, the oxidase mimetics have excellent reusability and reproducibility in cycle analysis.